Chinese Nationalism and Trust in East Asia. Issue 5 (20th October 2017) - Pang, Qin; Thomas, Nicholas
ABSTRACT: China's rise has been accompanied by a rise in nationalism. But what are the characteristics of this nationalism now being witnessed? Does it support China's constructive engagement with the international order, or does it seek to assert China's supremacy? These questions lie at the hub of a rapidly expanding secondary literature on the emergence of nationalism in China and its impact on China's foreign relations. What is, however, absent from the academic discourse is the voice of the Chinese people themselves. What are their perceptions of the nation-state, and how do these beliefs shape their views of China's relationship with East Asia? To address this gap, we conducted a series of large-scale surveys in Beijing between 2011 and 2013 on the twinned topics of domestic nationalism and international relations. Our findings, as reported below, represent an initial attempt to answer this final and, arguably, most critical set of questions.